Pengembangan Sistem Berbasis Web untuk Digitalisasi Promosi UMKM Kerajinan Souvenir Khas Toraja - Patresia Aris; La Ode Hasnuddin S. Sagala (Journal Research on Computing Knowledge, 2025)
The progression of information technology offers prospects for MSME participants to improve their competitiveness via digital marketing. This study seeks to create a web-based platform to promote MSMEs focused on Toraja souvenir crafts. The approach aims to tackle the limitations of traditional promotional strategies commonly employed by business proprietors, including word-of-mouth marketing and the utilization of social media without efficient inventory management. The system development adheres to the Waterfall methodology, which includes requirement analysis, system design, implementation, and testing phases. The primary features developed encompass product management, internet ordering, and a payment system. The system underwent evaluation through the black-box testing methodology to verify that all functionalities perform in accordance with specifications. The results demonstrate that the established system can enhance marketing efficacy and broaden the digital market presence of MSMEs. This technology enables business owners to handle their products more effectively and access a wider consumer base without geographical constraints